Ophthalmosaurian (Ichthyosauria) records from the Aalenian–Bajocian of Patagonia (Argentina): an overview - Fernández, Marta S. (2014)
Fil: Fernández, Marta S. Universidad Nacional de La Plata. Museo de La Plata. División Paleontología de Vertebrados. Buenos Aires, Argentina.